Liberia : 2019 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Liberia. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2019)
Liberia remains a fragile, post-conflict country with weak capacity and limited physical and human capital accumulation. External assistance to Liberia is winding down from its peak in 2016. To address pressing needs, the government launched its Pro-Poor Agenda for Prosperity and Development (PAPD), focusing on physical and human capital accumulation. Policy uncertainty and slippages, however, imposed a significant toll on the economy over the past two years. Particularly, higher fiscal deficits and accommodative monetary policy have led to rapid depreciation of the Liberia dollar and increased inflation, eroding the purchasing power of the poor.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet